Innovation of Islamic Education (PAI) Based on Multiple Intelligences - Abdul Basid (Didaktika Religia, 2017)
This article explores Islamic education based on multiple intelligences. Islam requires human orientation not only on the outcome but also the quality of process. It has been commonly known for several decades that the major experts in education use only intelligence quotient (IQ) tests as the sole measure in "judging" children's intelligence. It is even used as the main consideration and the only reference in predicting the future of children. In fact, especially for today's complex era, other factor intelligence can actually be a role for the future determinants of future children. This article discusses three important things, namely the basic concept of multiple intelligences, the new paradigm of learning Islamic Education, and PAI Learning based on various ideal intelligences. Multiple intelligence-based learning within the scope of an institution is generally not easy. Recently, Islamic Education as a subject or institution has its own advantages. They are the ability and sincerity to accommodate students who come from lower class society. Of course this is not fair if an Islamic Education institution or PAI subjects are forced to use certain modern theories but the income (money) and the quality of Islamic Education institutions and PAI teachers are not modernized.